Role of the Sympathetic Nervous Activity in Hypertension-Update in 2013 - Masuo, Kazuko; W. Lambert, Gavin (Current Hypertension Reviews, 2013)
Many reviews focused on the role of sympathetic nervous activity in hypertension have been published. Recently a new treatment, radiofrequency renal denervation for the treatment of resistant hypertension has been developed and examined in several clinical trials such as the Symplicity HTN and EnligHTN studies. In the Symplicity HTN-1 study the efficacy for lowering blood pressure remained satisfactory at 3 years follow up and many ancillary ameliorative effects have been reported including cardiovascular, psychosocial, and metabolic effects. The purpose of this review is to provide the current findings on the relationships between sympathetic nerve activity and hypertension, especially focus on the importance of renal sympathetic nervous activity for the onset and development of hypertension. In addition, the methods to assess sympathetic nervous activity are reviewed. The renal denervastion was developed for the treatment-resistant hypertensive patients, and excessive confidence of the efficacy and safety existed by the end of 2013, although several issues on the efficacy and safety were reported in 2014. Furthermore, long-term efficacy and impact on renal function have been unclear. Those issues have to be clear for clinical usage. This review will also address the recent data from the renal denervation.
Keywords: symplicity-1 study